THU0148 Increase of night qt-interval duration in rheumatoid arthritis patients treated with tofacitinib during 12-month follow-up. (15th June 2017) - Kirillova, IG; Novikova, D; Luchikhina, E; Markelova, E; Udachkina, H; Demidova, N; Misiyuk, A; Popkova, T; Volkov, A; Denisov, L; Karateev, D
Abstract : Objectives: to evaluate dynamic of ECG parameters in RA pts treated with tofacitinib (TOFA) during 12-month follow-up. Methods: After 12-m follow-up the ECG parameters by 12 lead ECG and 24h ECG was assessed in 28 RA pts treated with TOFA (22 women, median age 54 [40;62] years, disease duration 39, 5 [16, 5;60, 0] m, moderate to high activity (DAS28–5.1 [4.6;6.0], SDAI–26 (21;34)), positive for ACCP (75%)/RF (79%), who were non-responders to MTX at least 15 mg/week and/or other synthetic DMARDs and bDMARDs. TOFA therapy was started in all pts with dose 5 mg BID per os followed by the dose escalation to 10 mg BID in 8 (29%) pts. TOFA used in combination with MTX in 27 (96%) pts, leflunomide in 1 (4%). Low-dose oral corticosteroids (<10 mg/day prednisone or equivalent) were received by 9 (35%) pts. Remission or LDA was achieved in 55% pts (DAS28), 77% (SDAI). At baseline the most of pts had multiple CVRF and subclinical organ damage (arterial hypertension-67%, overweight-57%, abdominal obesity-61%, physical inactivity-64%, smokers/ex-smokers-25%/21%, menopausal status-59%, DM type 2–7%, mSCORE≥5%>21%, subclinical carotid atherosclerosis-64%, cardiac heart failure with preserved ejection fraction-7%. Cardioprotective therapy received 16 (57%) pts (beta-blockers–7, angiotensin II receptor type 2/ACE inhibitors–11, statins–11, dihydropyridine calcium channel blockers-7). Results: There was no difference in heart rate (HR), QTc interval duration, QRS duration measured by 12-lead ECG in RA pts treated with TOFA (table 1 ). However, an increase in PQ interval duration was observed (p=0, 04). There were significantly decrease of mean HR (p<0, 003), increase of QRS duration (p<0, 03), QTc (p<0.03), night QTc (p<0, 02) in 24 h ECG ambulatory recording. HR, PQ, QTc duration were changed independently of beta-blockers therapy. The number of pts with QTc≥440 ms increased from 11% to 21% (p>0.05). A change in QTc duration correlated negatively with dynamics of DAS 28, SDAI (r=-0, 4, p<0, 05), DM (r=0, 5, p<0, 02), dBP (r=-0, 4, p<0, 04). There were also significantly increase number of ventricular premature beats (p<0, 03). Conclusions: A significant decrease in HR and an increase in QRS, night QTc interval duration, number of ventricular premature beats by 24h ECG were observed in RA pts treated with tofacitinib (TOFA) during 12-month follow-up. QTc duration correlated with dynamic of disease activity, DM type 2 and diastolic BP. Disclosure of Interest: None declared